Monoacylglycerol Lipase Inhibition in Tourette Syndrome: A 12‐Week, Randomized, Controlled Study. Issue 10 (12th June 2021) - Müller‐Vahl, Kirsten R.; Fremer, Carolin; Beals, Chan; Ivkovic, Jelena; Loft, Henrik; Schindler, Christoph
Abstract: Background: Modulation of the endocannabinoid system via monoacylglycerol lipase inhibition with Lu AG06466 (formerly known as ABX‐1431) has previously been shown to reduce tics in patients with Tourette syndrome. Objective: The aim of this study was to evaluate the efficacy and safety of Lu AG06466 in reducing tics, premonitory urges, and comorbidities in patients with Tourette syndrome. Methods: This was a 12‐week, multicenter, randomized, placebo‐controlled, double‐blind clinical trial of Lu AG06466 given at two dose levels in 49 adults with Tourette syndrome. Results: Both treatment groups showed improvement on the Total Tic Score of the Yale Global Tic Severity Scale; the mean (95% CI) treatment difference at week 8 of 3.0 (0.1, 5.9) ( P = 0.043) favored placebo. No significant differences were seen for other endpoints assessing changes in tic severity, premonitory urges, quality of life, and common psychiatric comorbidities. Treatment with Lu‐AG06466 was generally safe. Conclusions: There was no evidence that Lu AG06466 has efficacy in suppressing tics. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society